1984
DOI: 10.2307/1389020
|View full text |Cite
|
Sign up to set email alerts
|

Violent Crime in the Western Energy-Development Region

Abstract: Case studies of “boom towns” in the western United States and the theory of social disorganization predict positive effects of recent growth and energy development on the violent crime rate in small towns and rural areas. Regression results, with controls for local characteristics prior to the energy boom of the 1970s, give little evidence of additive effects of recent growth and energy development on the violent crime rate in nonmetropolitan counties of the major energy-producing states. Long-standing structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…In contrast, the findings of this study support the idea that crime in energy extractive communities is more likely associated with enduring social structural factors. This is consistent with Wilkinson et al (1984) who found ''. .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the findings of this study support the idea that crime in energy extractive communities is more likely associated with enduring social structural factors. This is consistent with Wilkinson et al (1984) who found ''. .…”
Section: Discussionsupporting
confidence: 92%
“…Studies in the mid to late 1980s showed mixed evidence of the hypothesis (Smith, Krannich and Hunter 2001). For example, Smith, Krannich and Hunter (2001) noticed that crime rates and divorce rates did not increase in Western energy boom counties undergoing rapid population growth (Wilkinson et al ). Conversely, Freudenburg and Jones (:638) concluded that results from this research approach “all point to significantly greater increases in criminal activities than in populations.”…”
Section: Energy Boom and Crimesmentioning
confidence: 99%
“…Previous studies on boomtown crime have relied on three main approaches (Freudenburg and Jones 1991). The first relied on county-level data and compared growing counties against slow growing counties, such as Wilkinson et al (1984), Camasso and Wilkinson (1990), among others. The second employed survey data on criminal victimization, such as Krannich, Greider, and Little (1985) and Freudenburg (1986), among others.…”
Section: Energy Boom and Crimesmentioning
confidence: 99%
“…The focus on rural crime began in part with the interest of rural sociologists about the various impacts of rapid population and economic growth associated with energy development in small, western towns (Freudenburg & Jones 1991;Krannich, Berry & Greider 1989;Krannich, Greider & Little 1985;Seydlitz et al 1993;Wilkinson et al 1984). This has blossomed into a more general interest in rural crime vis-à-vis the relationship of social change and its impact on rural peoples and places (Arthur 1991;Barnett & Mencken 2002;Cancino 2005;Deller & Deller 2010;Donnermeyer, Jobes & Barclay 2007;Jobes et al 2004;Kowalski & Duffield 1990;Lee, Maume & Ousey 2003;Osgood & Chambers 2000;Rephann et al 1999;Resig & Cancino 2004;Wells & Weisheit 2004;Wilkinson 1984aWilkinson , 1984b.…”
Section: Introductionmentioning
confidence: 99%